Physical health perspective and mental subnormality of a child with Hunter’s disease - Wani, Gowhar Iqbal; Imran, Ayesha; Rathore, Vyas; Gupta, Anumodan (Indian Journal of Child Health, 2018)
Hunter’s disease or mucopolysaccharidosis (MPS II) is a rare X-linked recessive disorder caused by deficiency or malfunctioning of the lysosomal enzyme iduronate-2-sulfatase (IDS), leading to progressive accumulation of glycosaminoglycans in almost all cell types, tissues and organs which result in permanent, progressive cellular damage that affects the appearance, physical abilities, organ and system functioning and, in most cases, mental development. The common clinical presentations include facial dysmorphism, pulmonary dysfunction, hepatosplenomegaly, and skeletal defects including joint stiffness and contractures, cardiomyopathies, and neuropsychiatric manifestations. We present this case of MPS II with clinical presentation including coarse facies, short stature, and mental retardation. The diagnosis was confirmed by demonstrating the deficiency of IDS in plasma. We report this case to highlight the clinical features and to specify the mental and physical health perspective of a child with Hunter’s disease. Mental subnormality includes progressive cognitive deterioration that is not manageable with enzyme replacement therapy. Hence, the patient should undergo regular assessment and should be trained accordingly.